2015
DOI: 10.1158/0008-5472.can-15-0930
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Activation of TWIST1 by MTDH Promotes Cancer Stem–like Cell Traits in Breast Cancer

Abstract: Cancer stem-like cells (CSC) are a cell subpopulation that can reinitiate tumors, resist chemotherapy, and give rise to metastases. Metadherin (MTDH) contributes widely to tumor growth, drug resistance, relapse, and metastasis, but its molecular mechanisms of action are not well understood. Here, we report that MTDH drives CSC expansion by promoting the expression of TWIST1, a transcription factor critical for cancer cell stemness and metastasis. MTDH activates TWIST1 expression indirectly by facilitating hist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…Yoo et al (20) reported that MTDH is an interaction partner of p100 protein, a component of the RNA-induced silencing complex (RISC). MTDH also facilitates transcription by modulating transcription factors, such as TWIST1 and HIF1A, thereby controlling cancer cell migration, invasion, and angiogenesis during tumorigenesis (21,22). Because of the importance of MTDH in cancer development, novel regulators that modulate MTDH expression need to be further defined.…”
mentioning
confidence: 99%
“…Yoo et al (20) reported that MTDH is an interaction partner of p100 protein, a component of the RNA-induced silencing complex (RISC). MTDH also facilitates transcription by modulating transcription factors, such as TWIST1 and HIF1A, thereby controlling cancer cell migration, invasion, and angiogenesis during tumorigenesis (21,22). Because of the importance of MTDH in cancer development, novel regulators that modulate MTDH expression need to be further defined.…”
mentioning
confidence: 99%
“…In breast cancer cells, MTDH overexpression promoted cancer cells to undergo EMT, while MTDH knockdown reversed EMT changes [16]. In addition, MTDH could regulate TWIST expression in breast cancer cells [17]. MTDH promoted EMT of tongue squamous cell carcinoma (TSCC) through activating Wnt/PCP signaling pathway [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not exclude other mechanisms responsible for MTDH stimulated miR-130b expression, such as epigenetic mechanism. MTDH has been involved in epigenetic activation of TWIST1 [17]. In addition, numerous studies have indicated that epigenetic modifications such as aberrant DNA methylation and histone modification affect miRNA expression in cancer cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a putative correlation between p300 and Twist1 in the modulation of urothelial cancer invasiveness [11]. Epigenetic activation of Twist1 was confirmed by histone acetyltransferase CBP, which cooperated with metadherin to increase Twist1 expression in breast cancer [12]. Next, in an attempt to investigate the underlying role of Twist1 in progression of human gastric cancer, Qian et al identified the interaction of p300 with Twist1 by co-immunoprecipitation.…”
Section: Acetylation Of Twistmentioning
confidence: 99%